2011
DOI: 10.1590/s0100-204x2011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da cama e do ar em diferentes condições de alojamento de frangos de corte

Abstract: Resumo -O objetivo deste trabalho foi avaliar as condições iniciais de alojamento de aves, de um dia de idade, em termos da qualidade da cama de frango reutilizada e do ar, em aviários comerciais de produção com diferentes sistemas de ventilação mínima e tipologia, por meio de análise geoestatística. O experimento foi realizado em quatro aviários: Blue House I (T1) e Blue House II (T2), Dark House (T3) e Convencional (T4). As variáveis analisadas foram: pH, umidade, temperatura superficial e concentração de am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 19 publications
2
18
1
9
Order By: Relevance
“…The other water soluble-f N is mainly uric acid, which corresponds to 60 to 70 % of the N excreted by poultries (Nahm, 2003). Mowrer et al (2013) determined the forms of N in 118 samples of poultry litter and found that uric acid and ammonium represented 9.4 and 17.4 %, respectively, of the total N. Significant amounts of ammonium may be lost from this kind of organic waste, mainly under high temperatures (Oliveira et al, 2003;Carvalho et al, 2011). Thus, drying the material before analysis, even at temperatures in the range of 40 to 60 °C, may result in significant losses of N as ammonia (Wood and Hall, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The other water soluble-f N is mainly uric acid, which corresponds to 60 to 70 % of the N excreted by poultries (Nahm, 2003). Mowrer et al (2013) determined the forms of N in 118 samples of poultry litter and found that uric acid and ammonium represented 9.4 and 17.4 %, respectively, of the total N. Significant amounts of ammonium may be lost from this kind of organic waste, mainly under high temperatures (Oliveira et al, 2003;Carvalho et al, 2011). Thus, drying the material before analysis, even at temperatures in the range of 40 to 60 °C, may result in significant losses of N as ammonia (Wood and Hall, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Reused litter has a greater amount of excreta, and leads to high humidity and increased ammonia levels inside poultry houses ranging from 60ppm up to 100ppm, which is harmful for broilers health (CARVALHO et al, 2011). Therefore, zeolites are incorporated into litter to reduce ammonia and moisture levels, through its ability to adsorb ions and absorb water.…”
Section: Utilization In Poultrymentioning
confidence: 99%
“…These authors describe that CO and CO 2 inside buildings were within the acceptable limits for a good breeding stock development. CARVALHO et al (2011) evaluating air quality for first broiler housing, at varied minimum ventilation system and building typology (blue, dark and conventional house), concluded that used ventilation was not enough to assure air quality in the facilities.…”
Section: Resultsmentioning
confidence: 99%